ISOLASI, KARAKTERISASI DAN UJI ANTIMIKROBA BAKTERI ENDOFIT ASAL TUMBUHAN JOHAR (Cassia siamea Lamk.) - Nursanty, Risa; Suhartono, Suhartono (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2012)
Endophytic bacteria are of alternative of antimicrobial compound producers. Their existence in the medicinal plants of johar (Cassia Siamea Lamk.) enables to produce bioactive compounds simmilar to those contained by the host plants. It is necessary to isolate and characterize endophytic bacteria from johar. Methods consisted of samples sterilization, endophytic bacterial isolation, and characterization of the morphology and physiology of Endophytic bacteria. a total of seven isolates of endophytic bacterial isolates were obtained from the isolation of plant Johar. Isolates DC 2, DC 3 and BC 3 had antibacterial capabilities with inhibitory zone diameters of 5 mm, 8.5 mm and 11.5 mm respectively.